Impact of a dual-axis solar tracker and reflector glass on the performance of a 100Wp photovoltaic panel - Siagian, Parulian; Peranginangin, SIWAN B; Kusuma, Budhi Santri; Sianturi, Roy Lamrun (Politeknik Negeri Lhokseumawe, 2025)
Solar radiation varies by region, and photovoltaic (PV) panels typically achieve a maximum efficiency of 21%. This study examines the impact of a dual-axis solar tracker and 5mm reflector glass on the performance of a 100Wp photovoltaic system. The experiment was conducted for three days in September, involved placing reflector glass perpendicular to incoming sunlight to enhance light capture and thermal efficiency. Results showed that the system achieved a maximum efficiency of 19.31% at 10:00 AM on Day 2, with a peak power output of 31.08 W under an irradiance of 595.26 W/m². The lowest efficiency of 4.26% occurred at 8:15 AM on Day 3. The highest recorded temperature was 36.6°C, while the lowest was 30.4°C. The findings suggest that using a dual-axis tracker with reflector glass can improve PV panel efficiency and power generation by optimizing incident radiation and heat distribution